(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
A field experiment was carried out in the rainy season of 2019 in Gombe states, Nigeria. The experiment was carried out in Tal, Billiri Local Government, Gombe State. The aim of the experiment was investigate the performance of ten varieties of sesame. The ten different varieties were; E-8, NCRIBEN-01, NCRIBEN-02, NCRIBEM-031, YANDEV-55, EX-BR-1, EX-BR-2, E-SUDAN, 560-1 and LOCAL. The treatments were laid in a randomized complete block design with three replications. The treatments were combined to have 10 plots in a block with 1 meter between the block and 0.5 meters within the plots. The seeds were placed in 5cm depth at the spacing of 15 x 75cm. During the research growth parameters like plant height, number of leaves and number of branches were measured. Other growth parameters like days of 1st flower, 50% flower, days of maturity, number of capsule per plant, seeds per capsule, number of capsule per leaves axis, 1000 seed weight and seed yield were also recorded. The results of the experiment revealed that sesame generally responded to both varietal and fertilizer effects. All the parameters studied have significantly (Pâ‰¤0.05) responded to the varietal effects, here variety NCRIBEN-01 and E-8 were observed to perform higher in both growth parameters, yield related character and overall yield. Based on the result obtained it can be suggested that the use of E-8, NCRIBEN-01, NCRIBEN-02, NCRIBEN-031, YANDEV-55 will give high yield followed by EX-BR-1, EX-BR-2, E-SUDAN and 506-1 leading to optimum yield for farmers in Tal, Billiri Local